CREB1 and ATF1 Negatively Regulate Glutathione Biosynthesis Sensitizing Cells to Oxidative Stress - Zhao, Lina; Xia, Wenjun; Jiang, Peng (Frontiers in Cell and Developmental Biology, 2021)
The cAMP response element binding protein (CREB) family (ATF1 and CREB1) have been reported in a diverse group of tumors, however, the mechanistic basis for this remains unclear. Here we found that CREB1 and ATF1 unexpectedly regulate Glutathione (GSH) biosynthesis by suppressing the expression of f GCLM and GSS, two key enzymes of GSH biosynthesis pathway. Mechanistic studies reveal that GCLM and GSS are direct transcriptional targets of CREB1 and ATF1. Through repressing the expression of these two enzymes, CREB1 and ATF1 reduce the GSH biosynthesis and the capability of cells to detoxicate reactive oxygen species (ROS), thereby increasing cellular susceptibility to oxidative stress. Therefore, our findings link CREB1 family to cellular metabolism, and uncover a potential therapeutic approach by targeting GCLM or oxidative stress for the treatment of tumors with relatively high expression of CREB1 family proteins.